Shrinkage Characteristics and Abrasion Resistance of Porcelain Waste-Based Geopolymers Mortar Under Chemical Exposure - Klingsad, Rada; Israngkura Na Ayudhya, Borvorn (Salehan Institute of Higher Education, 2025)
This study investigated microstructural analyses, dry shrinkage, and autogenous shrinkage of mortar using defective sanitary ware porcelain as a low-calcium material with sodium hydroxide (NaOH) and sodium silicate (Na₂SiO₃). Additionally, the abrasive resistance of concrete was examined under chemical corrosion environments of 5%, 10%, 15%, and 20% H₂SO₄, HCl, and MgSO₄. The microstructural analyses using XRF, DTA-TGA, and SEM were conducted at 28 days. For specimen preparation, mortar specimens were oven-cured for 2 h at 105°C, while concrete specimens were oven-cured for 24 h and air-cured for 28 days before undergoing chemical immersion at 3, 7, 14, 21, 28, 60, and 90 days. NaOH concentrations of 8, 10, 12, and 14 Molar (M) were used. The results indicated that shrinkage in porcelain-based geopolymer mortars increased with higher NaOH concentration, and increasing the initial curing temperature led to increased mortar shrinkage. The autogenous shrinkage of 14M alkali-activated porcelain mortar was found to be higher than that of 8M, 10M, and 12M NaOH concentration mortars. Additionally, increasing the NaOH concentration reduced the abrasive resistance of the concrete. The maximum weight loss values were 8.21%, 6.91%, and 0.96% for 20% H₂SO₄ (90 days immersion), HCl (90 days immersion), and 20% MgSO₄ (90 days immersion), respectively. The microstructural findings confirmed the formation of gel-intact phases, highlighting the importance of curing time and NaOH concentration in low-calcium binder material. This study emphasized the critical role of curing temperature in optimizing the mechanical and durability properties of defective sanitary ware porcelain-based geopolymer.